Long-Term Catch-Up Weight Gain Following Fundoplication in Children - Kubiak, Rainer; Eaton, Simon; Andrews, James; Grant, Hugh W. (European Journal of Pediatric Surgery, 2013)
Background Laparoscopic fundoplication for severe gastroesophageal reflux (GOR) is well established in children. However, there are only a few reports on the long-term nutritional outcome following fundoplication. The aim of this study was to assess weight gain following fundoplication in children.Methods In this study, 127 children who underwent laparoscopic fundoplication ± gastrostomy between July 1998 and April 2007 were followed up for a median of 29.6 months postsurgery. Data (demography, weight) at fundoplication were collected prospectively, with ethical approval. Weights were converted to Z-scores for age (Z-score of 0 is equivalent to 50th percentile, −1 to 16th centile, and −2.0 is equivalent to 2nd centile). Severe failure to thrive (FTT) was defined as a Z-score of less than or equal to −2. Data were compared using the two-tailed Student t test, and multilevel regression modeling was applied.Results At the time of operation, patients had a low weight-for-age Z-score (−1.87 ± 0.19) and 61 children (48%) had FTT. Children who received a simultaneous gastrostomy had a significantly lower Z-score at operation (−2.80 ± 0.22) than those who did not (−0.68 ± 0.25, p < 0.001). Overall, patients exhibited significant catch-up weight gain following surgery (+0.88 ± 0.14, p < 0.001). The greatest increase in weight was mostly marked in patients who had a gastrostomy inserted (+1.22 ± 0.20, p < 0.001), but it was also significant in patients who did not receive a gastrostomy (+0.44 ± 0.17, p = 0.013). Catch-up weight gain occurred in neurologically impaired (NI) patients with (+1.31 ± 0.22, p < 0.001) or without (+0.81 ± 0.29, p = 0.012) gastrostomy. Weight of neurologically normal (NN) patients was within normal range but slightly lower than average before surgery (−0.45 ± 0.24) and this did not significantly change following surgery. There was no significant catch-up weight gain in patients (n = 9) with “esophageal pathologies” (Z-score of −1.35 ± 0.61 at operation compared with −0.35 ± 0.34 at follow-up; p = 0.14).Conclusions Laparoscopic fundoplication (with or without gastrostomy placement) resulted in significant weight gain in children with GOR. Insertion of a gastrostomy at the same time resulted in greater weight gain. Pronounced weight gain occurred in NI children, whereas NN children and those with esophageal pathologies did not demonstrate any significant benefit in terms of weight gain following fundoplication.
Keywords: laparoscopy; fundoplication; children; gastroesophageal reflux; weight gain